Synthesis and characterization of novel Co/Bi-layered double hydroxides and their adsorption performance for lead in aqueous solution - Amita Jaiswal; M.C. Chattopadhyaya (Arabian Journal of Chemistry, 2017)
The Co/Bi-layered double hydroxides (Co/Bi-LDH) were synthesized by co-precipitation method and used for the removal of lead from aqueous solutions. The Co/Bi-LDH was characterized using X-ray diffraction (XRD), Fourier Transform Infrared spectroscopy (FTIR), Transmission Electron Microscopy (TEM), Selected Area Electron Diffraction (SAED) and BET for textural properties. Adsorption of lead solution by Co/Bi-LDH was carried out using batch experiment by mixing the lead solution and the adsorbent. The effects of various parameters such as contact time, pH, adsorbent dosage and initial concentration were investigated. The optimum pH for lead removal was found to be 4 and the optimum time of lead removal was found to be 120 min. The isotherm data were analyzed using Freundlich and Langmuir. The adsorption isotherms can be well described by the Langmuir model with R2 > 0.99. Its adsorption kinetics followed the pseudo-second-order kinetic model. Thermodynamic parameters were also studied. It was found that the synthesized Co/Bi-LDH can reduce the lead concentration and makes it a potential material for the decontamination of lead polluted water.